A hybrid path planning algorithm considering AUV dynamic constraints based on improved A algorithm and APF algorithm - Zhang, Wei; Wang, Naixin; Wu, Wenhua (Ocean engineering, 2023)
Path planning is crucial for (autonomous underwater vehicles)AUVs to achieve autonomy. A proper path-planning method can obtain the optimal path while ensuring the safety of the path. This paper aims to address the issue of significant path-tracking errors arising from the independent research of traditional path-planning algorithms and path-tracking techniques. To this end, a path-planning algorithm based on A* + APF(AplusPF) is proposed for AUVs. This algorithm incorporates AUV kinetics into the iterative process of the A* algorithm and plans a safe and trackable path while fully considering AUV dynamic constraints and position and attitude information. Additionally, the algorithm adds the prediction of AUV trajectory to the heuristic function of the A* algorithm so that the heuristic function is closer to the actual value, thereby improving the algorithm's efficiency. The algorithm combines the APF algorithm to achieve fast and effective obstacle avoidance, thereby solving the problem of the A* algorithm's slow running speed in complex multi-obstacle environments. The effectiveness of the AplusPF algorithm is verified by the simulation results. •Taking AUV kinematics into account in path-planning algorithms.•The combination of the A* algorithm and APF algorithm realizes fast and effective obstacle avoidance.•Improved the A* algorithm to design a reasonable path that is more in line with AUV kinematics.